Comments on an Improved RFID Security Protocol for ISO/IEC WD 29167‐6. Issue 1 (1st February 2013) - Kang, You Sung; Choi, Dooho; Park, Dong‐Jo
Abstract : With the rapid progress of RFID security technologies, the international standard group ISO/IEC JTC 1/SC 31 is developing a few security technologies for RFID systems. One of the initial proposals is ISO/IEC working draft (WD) 29167‐6. Recently, Song and others stated that Protocol 1 of ISO/IEC WD 29167‐6 is vulnerable to a malicious adversary. However, their analysis comes from a misunderstanding regarding a communication parameter called Handle. In this letter, we point out that an adversary cannot obtain any sensitive information from intervening in Protocol 1.